There are currently no widgets assigned to the left-sidebar, place some!

Once you add widgets to this sidebar, this default information will go away.

Widgets can be added by going to your dashboard (wp-admin) -> Appearance -> Widgets, drag a widget you want to see into one of the appropriate sidebars.

psh still dealing with single variable math? I would make the problem more like finding the function of the normal plane to a point on a conic surface. ðŸ˜‰

not sure why everyone went to the trouble of some of those steps, and the initial problem wasn’t copied correctly, anyway
log 3 (3^(x+1) – 18) = 2
3^(log 3 (3^(x+1) – 18)) = 3^2
3^(x+1) – 18 = 9
3^(x+1) = 27
log 3 (3^(x+1) = log 3 (27)
x+1 = 3
x = 2

4 less steps.

Comments are closed.

Feeling lonely? Send me an email! commanderloochy@gmail.com

log 3 ( 3^(x+1) ) – 18 = 2

log 3 ( 3^(x+1) ) – 18 = log 3 (3^2)

3^(x+1) – 18 = 3^2

3^(x+1) – 18 – 3^2 = 0

3^(x+1) – 18 – 9 = 0

3^(x+1) – 27 = 0

3^(x+1) = 27

3^(x+1) = 3^3

x+1 = 3

x = 3-1

x = 2

Easier (for me):

log 3 (3^(x+1) – 18) = 2

3^2 = 3^(x+1) – 18

9 = 3^(x+1) – 18

3^(x+1) = 9 + 18

3^(x+1) = 27

3^(x+1) = 3^3

x+1 = 3

x = 3 – 1

x = 2

psh still dealing with single variable math? I would make the problem more like finding the function of the normal plane to a point on a conic surface. ðŸ˜‰

Psh, both of you guys got it wrong. It’s not log base 3, it’s log base 10 of 3(x^(x+1)-18).

x=(ln((100/3)+18)/ln3)-1.

log 3 ( 3^(x+1) ) – 18 = 2

log 3 ( 3^(x+1) ) – 18 = log 3 (3^2)

3^(x+1) – 18 = 3^2

3^(x+1) – 18 – 3^2 = 0

3^(x+1) – 18 – 9 = 0

3^(x+1) – 27 = 0

3^(x+1) = 27

3^(x+1) = 3^3

x+1 = 3

x = 3-1

x = 2

(I just copied and pasted the other 2 guys’ response to look smart)

Who needs math?

http://www.wolframalpha.com/input/?i=log3%283^%28x%2B1%29-18%29+%3D+2

I would rather have the password NOT the answer. Just for shits and giggles when they doubt themselves over and over again.

I’ve never enjoyd log related problems

not sure why everyone went to the trouble of some of those steps, and the initial problem wasn’t copied correctly, anyway

log 3 (3^(x+1) – 18) = 2

3^(log 3 (3^(x+1) – 18)) = 3^2

3^(x+1) – 18 = 9

3^(x+1) = 27

log 3 (3^(x+1) = log 3 (27)

x+1 = 3

x = 2

4 less steps.

Comments are closed.